Three case reports of different clinical applications of mineral trioxide aggregate - Antonijević Đorđe; Despotović Ana; Ćetković Dejan; Dožić Aleksandra; Milanović Ivana; Ilić Dragan (Serbian Medical Society - Dental Section, Belgrade, 2024)
Introduction Calcium silicate dental cements have a wide range of applications in clinical dentistry. Many formulations were developed in the last decade and successfully employed for dental healing. In this paper, several clinical applications of mineral trioxide aggregate (MTA+, Cerkamed, Stalowa Wola, Poland) were presented. Outlines of cases The first case report reflects the application of the MTA+ for the healing of the root perforation of the upper premolar. The second case report was the usage of MTA+ for indirect pulp capping in patient who came with pain of the tooth previously restored with composite filling. The third case report was a patient with periapical cystic lesion that was removed surgically and root canal filled retrogradely with MTA+. Conclusion Altogether, current calcium silicate based dental cements bear a great potential for solving numerous issues in the dental practice regarding huge or problematic defects of dentine or alveolar bone.